Environmental impact of refuse-derived fuel: A Qualitative review of public health risks, energy efficiency, and emission oversight in Indonesia - I Wayan Koko Suryawan (BIORE Scientia Publisher, 2025)
Refuse-Derived Fuel (RDF) has been increasingly promoted in Indonesia as an alternative waste-to-energy solution, particularly for industrial applications such as cement production. This study presents a qualitative narrative review that explores the multidimensional environmental impacts of RDF implementation, with a specific focus on the Indonesian context. Four key themes were examined: air pollution, public health risks, low energy efficiency, and the lack of emission monitoring and environmental oversight. Findings indicate that RDF combustion contributes to hazardous emissions, including dioxins, heavy metals, and fine particulates, especially where waste segregation is inadequate. Public health issues such as respiratory infections and long-term toxic exposure are exacerbated by weak regulatory systems and the absence of Continuous Emission Monitoring Systems (CEMS). Additionally, Indonesia’s high organic waste content undermines RDF’s energy efficiency and sustainability. The review concludes that RDF, in its current form, poses significant environmental and governance challenges and must be reevaluated through the lens of public health protection, regulatory reform, and circular economy principles.